A review of outcome following valve surgery for rheumatic heart disease in Australia - Russell, E.; Tran, L.; Baker, R.; Bennetts, J.; Brown, A.; Reid, Christopher; Tam, R.; Walsh, W.; Maguire, G. (2015)
Background: Globally, rheumatic heart disease (RHD) remains an important cause of heart disease. In Australia it particularly affects younger Indigenous and older non-Indigenous Australians. Despite its impact there is limited understanding of the factors influencing outcome following surgery for RHD. Methods: The Australian and New Zealand Society of Cardiac and Thoracic Surgeons Cardiac Surgery Database was analysed to assess outcomes following surgical procedures for RHD and non-RHD valvular disease. The association with demographics, co-morbidities, pre-operative status, valve(s) affected and operative procedure was evaluated. Results: Outcome of 1384 RHD and 15843 non-RHD valve procedures was analysed. RHD patients had longer ventilation, experienced fewer strokes and had more readmissions to hospital and anticoagulant complications. Mortality following RHD surgery at 30 days was 3.1 % (95 % CI 2.2 – 4.3), 5 years 15.3 % (11.7 – 19.5) and 10 years 25.0 % (10.7 – 44.9). Mortality following non-RHD surgery at 30 days was 4.3 % (95 % CI 3.9 - 4.6), 5 years 17.6 % (16.4 - 18.9) and 10 years 39.4 % (33.0 - 46.1). Factors independently associated with poorer longer term survival following RHD surgery included older age (OR1.03/additional year, 95 % CI 1.01 – 1.05), concomitant diabetes (OR 1.7, 95 % CI 1.1 – 2.5) and chronic kidney disease (1.9, 1.2 – 2.9), longer invasive ventilation time (OR 1.7 if greater than median value, 1.1– 2.9) and prolonged stay in hospital (1.02/additional day, 1.01 – 1.03). Survival in Indigenous Australians was comparable to that seen in non-Indigenous Australians.Conclusion: In a large prospective cohort study we have demonstrated survival following RHD valve surgery in Australia is comparable to earlier studies. Patients with diabetes and chronic kidney disease, were at particular risk of poorer long-term survival. Unlike earlier studies we did not find pre-existing atrial fibrillation, being an Indigenous Australian or the nature of the underlying valve lesion were independent predictors of survival.